Reconstruction of Power Legitimacy: Ibn Zubair's Study in the History of Islamic Caliphate - Isnaini, Iin; Izuddin, Muhammad (Universitas Islam Negeri Sumatera Utara, 2025)
This paper aims to reconstruct the history of the Islamic caliphate with a focus on Ibn Zubair's conception of leadership selection and power legitimacy. The key issues discussed include how Ibn Zubair obtained his legitimacy and the principles he adhered to in selecting leaders, as well as the impact of his views on the political and social developments of the time. The research employs a qualitative method with a descriptive-analytical approach, involving literature reviews and text analysis. The primary sources consist of historical literature and records in the form of classical Islamic texts, while secondary sources are used to provide broader context. The findings reveal that Ibn Zubair had a deep understanding of leadership selection, which involved consultation and specific criteria for a just leader. The study concludes that Ibn Zubair supported the election of leaders through consensus within the Muslim community, prioritizing leadership quality and legitimacy from society, rather than hereditary succession as practiced by the Umayyad Dynasty, which tended to pass power from one generation to the next. Ibn Zubair’s thoughts significantly contribute to our understanding of power legitimacy in the history of the Islamic caliphate and its relevance to the current political and social context.